Teori modal budaya Pierre Bourdieu sebagai penguatan budaya pada anak dalam pendidikan keluarga Kristen - Aponno, Simon (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2025)
Family education plays a vital role in shaping children's charac-ter and identity, including by strengthening a culture aligned with Christian values. Pierre Bourdieu's theory of cultural capital offers a relevant perspective on how cultural heritage is transmitted within Christian families, shaping children's identities and moral values. This research aims to analyze the role of cultural capital in Christian family education as a means of strengthening children's culture. The method used is a literature study. The results revealed that cultural capital, comprising habitus, symbolic capital, and social practices, shapes the mindsets, habits, and values that children adopt in daily life. In the context of Christian family education, cultural capital can be realized through the habituation to Christian values, the use of faith language in family communication, and children's involvement in Christian religious and cultural practices. This study recommends that future research examine education within Christian families more comprehensively, drawing on Pierre Bourdieu's theory of cultural capital. Abstrak Pendidikan keluarga memiliki peran penting dalam membentuk karakter dan identitas anak, termasuk dalam memperkuat budaya yang selaras dengan nilai-nilai Kristen. Teori modal budaya Pierre Bourdieu menawarkan perspektif yang relevan dalam memahami bagaimana warisan budaya ditransmisikan dalam keluarga Kristen guna membangun identitas dan nilai-nilai moral anak. Penelitian ini bertujuan untuk menganalisis peran modal budaya dalam pendidikan keluarga Kristen sebagai upaya penguatan budaya pada anak. Metode yang digunakan studi kepustakaan. Hasil penelitian mengungkapkan bahwa modal budaya yang meliputi habitus, kapital simbolik, dan praktik sosial berkontribusi dalam membentuk pola pikir, kebiasaan, serta nilai-nilai yang dianut oleh anak dalam kehidupan sehari-hari. Dalam konteks pendidikan keluarga Kristen, modal budaya dapat diwujudkan melalui pembiasaan nilai-nilai Kekristenan, penggunaan bahasa iman dalam komunikasi keluarga, serta keterlibatan anak dalam praktik keagamaan dan budaya Kristen. Rekomendasi penelitian ini agar penelitian berikutnya mengkaji secara aktual dan luas tentang Pendidikan dalam keluarga Kristen berbasis teori modal budaya Pierre Bourdieu.